Analysis of the Hardness of AISI 4140 Steel Gears after Carbon Enrichment Using Coconut Shell Charcoal - Supriadi Supriadi; Mukhnizar Mukhnizar; Veny Selviyanty (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Carbon steel is widely used in engineering and industrial applications, particularly in machine component. One of the most important properties of steel is its strength. In addition to having good resistance to friction, steel is also required to possess adequate hardness. However, excessive hardness may lead to increased brittleness AISI 4140 steel is an alloy steel known for its good strength and toughness, nevertheless, in certain application, it still requires improved surface hardness to enhance wear resistance and extend component service live. This study aims to analyse the hardness improvement of AISI 4140 steel gears after carbon enrichment though a carburizing process using coconut shell charcoal as the carbon source, followed by aquenching process with three different cooling media air, water and new oil. The experimental method with solid carburizing technique was applied at a temperature of 900⁰ C and a holding time of 2 hours. Hardness teting was performed using the Vickers method to determine the changes before and after treatment. The results indicate that air cooling resulted in a hardness of 226,63 HV, showing a decrease of – 1,2 % compared to untreated speciments 229.57 HV. Water cooling produced a hardness of 234,83 HV, corresponding to an increase of 234,83 HV, corresponding to an increase of 2.29 %. Meanwhile, oil cooling resulted in the highest hadness value of 239,60 HV, withan increase 436 %.